Eco-Economic Systems of Russian Agriculture: Statistical Analysis - Dumnov, Aleksandr Dmitrievich; Khoruzhi, Lyudmila Ivanovna; Kharitonova, Anna Evgen’evna; Ukolova, Anna Vladimirovna; Skachkova, Svetlana Aleksandrovna (Journal of Reviews on Global Economics, 2019)
Over the recent 25 years Russia has experienced economic transformations that significantly have changed the impact of business activities on the state, structure, quality and use of natural resources: an annual decrease in the sizes of agriculturally used areas, reduction of soil fertility, destruction of the amelioration system, etc. Certainly, all this affects the economy and makes it necessary to investigate these interrelated processes in the context of an ecological-economic system. The article presents a multilateral statistical analysis of the eco-economic system of Russia, offers recommendations for improvement of the indicator system, analytical methodologies as well as proposals for implementation of the international standards into Russian statistics. It is emphasized that the asset value accounting philosophy should be developed on the basis of the specific nature of Russian statistics with application of the international practices. The article offers to start developing the macroeconomic accounts from the municipal level and then to aggregate the information at the level of a region and the country.